Homonota darwini macrocephala n.subsp. del noroeste argentino (Sauria, Gekkonidae) - Cei, José Miguel Alfredo María (1978)
A subspecific status is proposed for Homonota darwini population from ESE Salta (El Quebrachal), Argentina. Its racial position, formerly suggested by Kluge (1965), is supported by the allopatric condition and the several significant, diverging morphological traits. Homonota darwini macrocephala n. subsp. is recognized by its smaller size, the larger head, the less prominent snout and wider eye, the low number of paravertebral scales from axila- to groin, the smooth, faintly differentiated dorsal scales, and a brownish coloration, with irregular, dark transverse bands on the back.